HYGIENIC ANALYSIS OF THE DAILY NUTRITION OF MILITARY SERVICEMEN WITH HYPERTENSION IN THE SUMMER SEASON - Ermatov Nizom Jumakulovich; Turakulov Erkin Khasanovich (Innovate Conferences, 2025)
Protection and strengthening of the health of the working-age population, which forms the basis of the economic well-being of society, is one of the priority problems of forming the health of the nation. This problem is one of the urgent problems that must be solved separately among those with hazardous professions, including military personnel. Service and combat operations are characterized by the constant readiness of military personnel for emergency actions, the impact of a complex of negative factors of the production environment and the labor process. Assessment of the nutritional status of patients with cardiovascular diseases associated with the working conditions of military personnel is one of the urgent problems.